1989
DOI: 10.1080/03014223.1989.10422910
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for diapause in indiginous New Zealand insects: A review

Abstract: Recent experimental work suggesting the presence of diapause in indiginous New Zealand phytophagous insects is reviewed. This reopens the question of the frequency of true diapause in New Zealand insects; this is discussed in relation to other cases ofdiapauseand overwintering in New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…This shape corresponds to a type 1 photoperiodic response curve for diapause induction (Beck 1980) with a critical daylength of around 14-15 h. This similarity in the shape of the photoperiodic response curve as well as the increase in larval duration and number of moults required for development could point to a larval diapause being present in P. excessana. Diapause in New Zealand insects Incidences of overwintering in New Zealand insects have been reviewed by Roberts (1978) and Morris (1989). While overwintering was found in a great many species, few conclusive cases of diapause were found.…”
Section: Discussionmentioning
confidence: 99%
“…This shape corresponds to a type 1 photoperiodic response curve for diapause induction (Beck 1980) with a critical daylength of around 14-15 h. This similarity in the shape of the photoperiodic response curve as well as the increase in larval duration and number of moults required for development could point to a larval diapause being present in P. excessana. Diapause in New Zealand insects Incidences of overwintering in New Zealand insects have been reviewed by Roberts (1978) and Morris (1989). While overwintering was found in a great many species, few conclusive cases of diapause were found.…”
Section: Discussionmentioning
confidence: 99%
“…Gardiner (1970) reared 49 species of cerambycid on artificial diets and found that most species completed their life cycle in less than half the normal time under laboratory conditions. Further, daylength has been shown to affect the development of some cerambycid larvae and other New Zealand insects (Morris 1989;Yoshinori & Yukio 1997). Hence, although the majority of the larvae were reared in complete darkness (L:D 0:24 h) to match natural conditions within timber, one sample of larvae was reared under a 16:8 h L:D photoperiod.…”
Section: Introductionmentioning
confidence: 99%
“…Although diapause does not feature strongly in indigenous species, it is retained by exotic species in NZ (Morris 1989). Should the species in a biological control system have contrasting factors regulating diapause, then it is possible for a large mismatch, control failure and local extinction.…”
Section: Climate Variabilitymentioning
confidence: 96%